Tuning of morphology and polymorphs of carbonate/polymer hybrids using photoreactive polymer templates1. Issue 36 (28th September 2015) - Sakamoto, Takeshi; Nishimura, Yosuke; Kato, Takashi
<x xml:space="preserve">Abstract</x> Crystallization of inorganic carbonates on photolithographic polymer matrices led to development of inorganic/organic hybrid materials with photo-controlled and self-organized structures.